Severe joint deformity and patient global assessment of disease are associated with discrepancies between sonographic and clinical remission: A cross-sectional study of rheumatoid arthritis patients. Issue 2 (4th March 2021) - Nakabo, Shuichiro; Tsuji, Yuko; Inagaki, Maiko; Tsuji, Hideaki; Nakajima, Toshiki; Murakami, Kosaku; Terao, Chikashi; Hashimoto, Motomu; Furu, Moritoshi; Tanaka, Masao; Ito, Hiromu; Fujii, Takao; et al.
Abstract: Objective: Although recent clinical trials showed that ultrasound (US) remission is not required to achieve good outcomes at the group level, it currently remains unclear whether the prognosis of individual patients in clinical remission, but not US remission, i.e. those with subclinical sonographic synovitis (SSS), is favorable. However, it is no longer acceptable to perform US on all patients in order to identify those with SSS. Therefore, the present study was initiated to elucidate the conditions under which SSS is frequently detected. Methods: In total, 563 consecutive RA patients were recruited. Bilateral 2-5 MCP, wrist, ankle, and 2–5 MTP joints were scanned by US, and Gray scale and Power Doppler (PD) images were scored semi-quantitatively. Clinical data were obtained by physicians who were blind to US results. Changes in the modified Total Sharp Score (mTSS) of tocilizumab (TCZ) users were calculated. Results: A total of 402 patients were included. SSS was more frequently detected in patients with more severe joint deformity, even if they were in remission. In contrast, a high Patient Global Assessment of Disease (PtGA) did not reflect SSS. Furthermore, the relationship between PtGA and PD scores was weak. Although the frequency of SSS was high in TCZ user, the presence of SSS in TCZ users not always results in the progression of mTSS. Conclusions: While remission is overestimated in patients with severe joint deformity, underestimations may occur in those who do not fulfill remission criteria because of a high PtGA.